Pragmalingvistični vidiki računalniško posredovanega komuniciranja - Praprotnik, Tadej (Monitor ISH, 2007)
The article deals with certain characteristics of computer-mediated communication. Due to the predominantly textual character of this communication, the central interest is the linguistic practices formed in the virtual space of the Internet. The focal points are some concepts known from the pragmalinguistic theory: conversational maxims, phatic communion, politeness, with an emphasis on the distinction between synchronous and asynchronous types of on-line communication, which partly influences the formation of the corresponding linguistic practices. The article also highlights the issue of flaming, i.e. of hostile and aggressive, antinormative, on-line communication.
Keywords: internet; e-forumi; klepetalnice; računalniško komuniciranje; računalniško posredovana komunikacija